New perspectives on the regulation of germinal center reaction via αvβ8- mediated activation of TGFβ - This, Sébastien; Paidassi, Helena (Frontiers in Immunology, 2022)
Transforming growth factor-β (TGFβ) is a long-known modulator of immune responses but has seemingly contradictory effects on B cells. Among cytokines, TGFβ has the particularity of being produced and secreted in a latent form and must be activated before it can bind to its receptor and induce signaling. While the concept of controlled delivery of TGFβ signaling via αvβ8 integrin-mediated activation has gained some interest in the field of mucosal immunity, the role of this molecular mechanism in regulating T-dependent B cell responses is just emerging. We review here the role of TGFβ and its activation, in particular by αvβ8 integrin, in the regulation of mucosal IgA responses and its demonstrated and putative involvement in regulating germinal center (GC) B cell responses. We examine both the direct effect of TGFβ on GC B cells and its ability to modulate the functions of helper cells, namely follicular T cells (Tfh and Tfr) and follicular dendritic cells. Synthetizing recently published works, we reconcile apparently conflicting data and propose an innovative and unified view on the regulation of the GC reaction by TGFβ, highlighting the role of its activation by αvβ8 integrin.